Spatial Analysis of Cob-Douglas Production Function in Agriculture Sector of Nepal: An Empirical Analysis - Sharma Wagle, Thakur Prasad (Journal of Advanced Academic Research, 2017)
This paper examines use of the Cob-Douglas production function on the agricultural production in various space and dimensions. The objective of this study is to investigate the logical relationship between production and expenditure as well as labour. This research is to develop aunorthodox model for production function in Nepal. Analysis of the basic model used for estimation, estimates of elasticity of substitution equation on National agricultural panel data from economic survey (1983/84 – 2013/14) in averages. The empirical regression reveals that, sum of the regression coefficients is less than unity i.e., 0.976. So, system is less efficient or ‘diminishing return to scale. In fact, for every 100 percent of inputs increases (agriculture expenditure and labour) we can expect only 97.60 percent of output (GDP contribution from agriculture). This is a less efficient trend of the agriculture production in developing country like Nepal. It is clear to see that the Checking results consistency with theory and Robustness of the conclusion. Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 104-114